2012
DOI: 10.1037/a0029470
|View full text |Cite
|
Sign up to set email alerts
|

Maternal history of parentification, maternal warm responsiveness, and children's externalizing behavior.

Abstract: Destructive parentification occurs when children are expected to provide instrumental or emotional caregiving within the family system that overtaxes their developmental capacity. According to parentification theory, destructive parentification in family of origin poses a risk to child development in subsequent generations; however, there is a paucity of empirical research examining the impact of a maternal history of destructive parentification on parenting quality and child outcomes in subsequent generations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 55 publications
(95 reference statements)
2
36
0
1
Order By: Relevance
“…Whereas previous studies have identified mediators of the association between maternal history of parentification and offspring externalizing (e.g., Nuttall et al, 2012), contexts that moderate this association have not yet been examined. The present study sought to identify which children in the second generation are most at risk to maladaptation in the context of risk posed by maternal history of filial responsibility.…”
Section: Moderation Of Intergenerational Riskmentioning
confidence: 99%
See 4 more Smart Citations
“…Whereas previous studies have identified mediators of the association between maternal history of parentification and offspring externalizing (e.g., Nuttall et al, 2012), contexts that moderate this association have not yet been examined. The present study sought to identify which children in the second generation are most at risk to maladaptation in the context of risk posed by maternal history of filial responsibility.…”
Section: Moderation Of Intergenerational Riskmentioning
confidence: 99%
“…When children's temperament is not respected and accommodated by parenting, children are at risk for emotional adjustment difficulties (Chess & Thomas, 1991;Thomas & Chess, 1977). Given the increased needs of children with difficult temperament and the rearing environment characterized by poor warmth and responsiveness provided by mothers with a history of parentification (Nuttall et al, 2012(Nuttall et al, , 2015, there may be an elevated risk for poor parent-child goodness of fit. As such, children with difficult temperament may be especially susceptible to increased externalizing symptomatology in the context of the risk posed by maternal filial responsibility history.…”
Section: Moderation Of Intergenerational Riskmentioning
confidence: 99%
See 3 more Smart Citations